2015
DOI: 10.1111/cod.12401
|View full text |Cite
|
Sign up to set email alerts
|

Is p‐tert‐butylphenol‐formaldehyde resin (PTBP‐FR) in TRUE Test® (Mekos test) sensitizing the tested patients?

Abstract: Retesting did not add information regarding causes of possible sensitization. Analysis showed that the resin used in TRUE Test® has a lower degree of polymerization or condensation, which may enhance its sensitizing properties. A follow-up of late reactions to PTBP-FR in TRUE Test® should be carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Allergy to PTBP‐FR was also common in adolescents in this study. This allergy has not been shown to be so prevalent in previously published population‐based studies [0.9% in a study performed in 1995–1996 ; 1.4% in 2000–2001 ], with the exception of one, where the prevalence was exceedingly high (13.8%) . Because of the late development of some reactions in previous studies, patch test sensitization has been suggested as an explanation .…”
Section: Discussionmentioning
confidence: 88%
“…Allergy to PTBP‐FR was also common in adolescents in this study. This allergy has not been shown to be so prevalent in previously published population‐based studies [0.9% in a study performed in 1995–1996 ; 1.4% in 2000–2001 ], with the exception of one, where the prevalence was exceedingly high (13.8%) . Because of the late development of some reactions in previous studies, patch test sensitization has been suggested as an explanation .…”
Section: Discussionmentioning
confidence: 88%
“…Active sensitization is thought to be uncommon, amounting, according to some series, to 0.1% of all reactions . Some allergens have been associated more frequently with active sensitization, such as p ‐phenylenediamine , acrylates , p ‐ tert ‐butylphenol‐formaldehyde resin , chloracetamide , isothiazolinones , and Primula extracts . The literature concerning active sensitization is sparse and confusing, being almost exclusively based only on isolated cases or retrospective studies .…”
Section: Discussionmentioning
confidence: 99%
“…Six months before testing, one of the latter subjects (subject 1) had purchased a watch strap to which she had developed an eczematous reaction. Although the authors stated in the brief case report that the strap was sent for chemical analysis, they did not identify the contents, and indicated that the results 'possibly indicated active sensitization to the PTBP-FR' (1). From the results of the gas chromatographic-mass spectrometric analysis, we later learned that PTBP-FR monomers were present in the glue of the watch strap, which the authors estimated contained 80 mg of PTBP-FR.…”
mentioning
confidence: 98%
“…To the Editor, A recent article on p-tert-butylphenol-formaldehyde resin (PTBP-FR) in TRUE Test ® suggests that this patch may be sensitizing patients on whom it is tested (1). As the manufacturer of this product, I would like to point out a few additional considerations.…”
mentioning
confidence: 99%
See 1 more Smart Citation